Imitanciometria com sonda de baixa e alta frequência em lactentes com indicadores de risco para a deficiência auditiva - Carmo, Michele Picanço do (2009)
Introduction: Tympanometry is effective in early identification of external and middle ear diseases and its use is very established for children and adults. However for newborns and infants, some controversies remain. Many studies recommend 1000Hz tympanometry probe for infants under six months old because it shows higher sensibility and accuracy to identify correctly middle ear diseases in this population. Goal: The goal of the present study was to analyze results of tympanometry with 226Hz and 1000Hz probe tone in infants under six months old. Method: 142 infants (245 ears), 70 girls and 72 boys, age range between 12 and 180 days old with risk indicators associated with hearing loss. In the hearing screening were accomplished the following exams: Transient Otoacoustic Emissions, and Automatic Auditory Brainstem Response in 35dBNA. Tympanometric curves were classified in A, Flat, C, Double Peak, Asymmetric, Inverted, and also as normal and abnormal. Tympanometry peak pressure was analyzed. Results: otoacoustic emissions were present in 211 ears (group 1) and absent in 34 ears (group 2). Results with 226Hz probe tone revealed: in the group 1- 130 (61,61%) tympanograms type A, 67 (31,75%) double peak, 12 (5,69%) flat tympanograms and 2 type C (0,95%), in the group 2- it was found 19 curves type A (55,88%), 6 curves type double peak (26,47%), 4 flat tympanograms (11,76%) and 2 type C (5,88%). The 1000Hz probe tone revealed: in the group 1- 83 curves type A (76,85%), 7 curves were asymmetric (6,48%), 4 curves with double peak (3,70%), 10 flat tympanograms (9,26%), 3 type C (2,78%) and 1 inverted curve (0,93%), in the group 2- 2 curves type A (14,29%), 2 asymmetric tympanograms, 6 flat tympanograms (42,86%), 2 type C (14,29%) and 2 inverted tympanograms (14,29%). For the curves classification in normal or abnormal, with 226Hz probe tone, for group 1, 130 ears (90,28%) were normal and 14 (9,72%) were abnormal. In the group 2, 19 ears (76%) continued normal and only 6 (24%) were abnormal. With 1000Hz probe, in group 1, 162 ears (83,94%) were normal and 31 (16,06%) abnormal. In group 2, only 7 ears (25,93%) were normal and 20 abnormal (74,07%). Tympanometry peak pressure obtained with 1000Hz presented higher values and greater variability than 226Hz. It did not demonstrate significant difference in results between right and left ears, neither with 226Hz nor with 1000Hz. Although alterations in pressure can affect transient otoacoustic emissions results, some ears with negative pressures (smaller than -100daPa) were present in otoacoustic emissions. Conclusion: The 1000Hz probe tone presented larger sensibility to identify correctly abnormal tympanometrics curves, in the group with present otoacoustic emissions, as well as with no emissions; Unlike 1000Hz, in infants with no otoacoustic emissions, prevailed abnormal tympanometry. From this research, it is possible to conclude that 1000Hz probe tone is more adequate to evaluate newborns and infants under six months